2016
DOI: 10.1111/jfpp.12777
|View full text |Cite
|
Sign up to set email alerts
|

Obtention of Natural Dyes from Industrial Blackberry Pulp Residues (Rubus sp)

Abstract: The fruit processing industry generates large amounts of waste residues carrying environmental and financial costs. These residues, like a waste of blackberry pulp processing are composed mostly of peels and seeds rich in pigments and antioxidants, representing a potential source of natural dyes. We used complete experimental design and response surface methodology to evaluate how the quantity of solvent (20–50 mL), number of extractions (1–5), and time (10–30 min) affect the anthocyanin yield from blackberry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Freeze-dried BP was characterised by a significantly higher redness and less blueness value in comparison with elderberry and chokeberry powder as shown in an earlier study (Różyło et al, 2019). Another study (de Vargas, Jablonski, Flôres, & de Rios, 2017) reported that the peels and seeds of blackberry are rich in pigments and antioxidants, representing a potential source of natural dyes. Blackberries are a great source of anthocyanin pigments (Fan-Chiang & Wrolstad, 2006), and the content of these pigments plays a critical role in determining the colour quality of many fresh and processed fruits (Giusti & Wrolstad, 2005).…”
Section: Colour Parameters Of Freeze-dried Blackberry Powdermentioning
confidence: 76%
“…Freeze-dried BP was characterised by a significantly higher redness and less blueness value in comparison with elderberry and chokeberry powder as shown in an earlier study (Różyło et al, 2019). Another study (de Vargas, Jablonski, Flôres, & de Rios, 2017) reported that the peels and seeds of blackberry are rich in pigments and antioxidants, representing a potential source of natural dyes. Blackberries are a great source of anthocyanin pigments (Fan-Chiang & Wrolstad, 2006), and the content of these pigments plays a critical role in determining the colour quality of many fresh and processed fruits (Giusti & Wrolstad, 2005).…”
Section: Colour Parameters Of Freeze-dried Blackberry Powdermentioning
confidence: 76%
“…Carmine, a lake of carminic acid calcium aluminium, is insoluble in water but may be used in meat, sausage, topping, dairy goods, desserts, and other products. [83,84]. It was also used in the production of canned fruit such as cherries, jams, pulp, and so on [85].…”
Section: Foodmentioning
confidence: 99%
“…Some food industries use dyes obtained from natural sources. This can generate opportunities for the development of food products with positive economic and environmental impacts [ 92 ]. This trend can be seen in some products in the supermarket, such as dry pasta that is naturally colored with dry tomatoes and spinaches.…”
Section: Why Use Tomatoes As Food Coloring?mentioning
confidence: 99%